DAMPAK POLA TANAM PADI – PADI DAN PADI – SEMANGKA TERHADAP Al DAN Fe PADA KONDISI TANAH TIDAK DISAWAHKAN DI DESA AIR HITAM KECAMATAN LIMA PULUH KABUPATEN BATUBARA - Rizki Annisa Nasution; M. M. B. Damanik; Jamilah Jamilah (Jurnal Agroekoteknologi, 2014)
Several farmers in the Village of Air Hitam Sub District of Lima Puluh District of Batubara wereused the impact of Rice-Watermelon cropping system because production of rice was descended inevery years and to increasing the use irrigate efficiency. The difference in cropping system and thelong inundation result differences paddy soil properties. This research analyzed the soil pH, Al-dd,Al saturation, Fe3+, and Cation Exchange Capacity (CEC) of land in the village of Air HitamSub District of Lima Puluh District of Batubara with altitude of 14 meters above sea level. Theresearch start to do on May until November 2012. The results of analyzed was procced by t-analyze.The showed that soil pH, Fe3+, CEC on Rice-Rice cropping system is lower than the Rice-Watermelon, while Al was higher in Rice- Rice cropping system than Rice- Watermelon.Keywords: Al, Fe, paddy soil, cropping system